Unique Denture Identification System for All Indian Nationals - Pathak, Chetan (Contemp Clin Dent, 2018)
Marking dental prosthesis has always been considered an important part of forensic dentistry. Denture identification systems are important not only for patients in health-care facilities, old-age homes, and hospitals but also in medico-legal cases. In India, no standardized method is being followed for labeling of the dentures. This article proposes a technique of denture marking that gives permanent, unique, and global identification to all the Indian nationals using Aadhaar - a universally accepted identity for Indian nationals. The information on the card can be printed on a piece of paper or a plastic card and the Aadhaar card quick read code/number can be easily and cost-effectively used for marking all the newly constructed or existing prosthetic devices.